INFLUENCE OF MACROECONOMIC VARIABLES ON EXCHANGE RATE: A STUDY ON BANGLADESH - Hasan, Shaikh Masrick; Islam, Roushanara (International Journal of Accounting & Finance Review, 2023)
Exchange rate plays an imperative role in international trade of the country. The exchange rate is an important macroeconomic variable used as parameter for determining international competitiveness and indicates the global position of economy of the country. The development of the country is closely related with its foreign exchange system. The construction of this study is to determine the influential macroeconomic variables of the exchange rate by considering 20 years, from 2002 to 2021, data of Bangladesh. Pearson’s correlation and multiple linear regression are used to analyse the data. The results indicate that current account balance, foreign exchange reserve, remittances, and GDP growth rate has a significant positive correlation with the exchange rate. However, interest rate and current account balance have no statistically significant relationship with the exchange rate. Therefore, current account balance, foreign exchange reserve, remittances, and GDP growth rate are the most influential factors in determining the exchange rate. Therefore, this research concludes that policymakers can change these influential factors to get the best exchange rate for the benefit of the growing economy of Bangladesh. JEL Classification Codes: B22, O24.